Fungsi Komunikatif Eufemisme dalam Bahasa Minang Sebagai Cerminan dari Tradisi Timur - Karnaen, Delvi Melina; Anayaty, Wan; Mulia, Hendra (Universitas Harapan Medan, 2023)
This paper examines the refinement of language which is more polite expressions to avoid statement that are felt rude, which is a thesis entitled “Communicative Functions of Euphemism in Minang Language as a Reflection of Eastern Tradition”. This research uses a semantic approach, identifying the form of euphemism in Minang Language. The basis of the theory used is using the theory of Allan and Burridge (1991), in this theory explaining the function of euphemisms. This guides the community to have a more polite attitude in speaking. This manners in speaking are called Langgam Kato, namely Kato Mandaki (which is a greeting word used for people who are older or of higher social status), Kato Manurun (a greeting word used for people who are younger or of lower social status), Kato Malereng (which is a greeting word used for people who are in the same position and respect each other in a family relationship) and Kato Mandata (a greeting word used for people who are the same age or the same in terms of age, social status and closer relationship or familiar).